Characteristics, distribution and diagenetic stages of chert in the La Silla Formation (Lower Ordovician), Argentine Precordillera - Mariana M. Raviolo; José A. Barbosa; Virgínio H. Neumann (Anais da Academia Brasileira de Ciências, 2009)
The late Cambrian - late Tremadocian La Silla Formation is a carbonate unit of the eastern Precordillera in Argentina whose facies indicate a shallow platform environment. Until this moment, there were no studies that referred to the diagenetic evolution of these rocks. The present study involves the characteristics and distribution of the silicification that affects this unit and determines its different diagenetic stages through petrographic (with cathodoluminescence support) and stratigraphic analyses. An early diagenetic chert, in a stage previous to the compactation, was observed. This chert is related to silica-rich seawater in contact with permeable and porous sediments. A later pulse of chert, associated with fracturing, also occurs. The knowledge provided by the characteristics and distribution of chert in these carbonates is significant, especially when considering that the La Silla Formation in San Juan province is the most quarried unit for the elaboration of lime. A Formação La Silla (Neo Cambriano-Neo Tremadociano) é formada por depósitos carbonáticos da região da Pré-Cordilheira leste, Argentina. As faciologias encontradas em tais depósitos indicam um ambiente de deposição caracterizado por uma plataforma rasa. Até o momento, nenhum estudo tratou especificamente da evolução diagenética dessas rochas. O presente estudo envolve as características e distribuição da silicificação que afeta esta formação e apresenta os diferentes estágios diagenéticos ocorridos, através de análises petrográficas (auxiliadas por catodoluminescência) e estratigráficas. Foi identificado um pulso precoce de silicificação, anterior ao processo de compactação das rochas afetadas. Esta silicificação foi favorecida pela presença de água do mar rica em sílica em contato com sedimentos porosos e permeáveis. Também foi identificado um pulso de silicificação tardia, associado a eventos de fraturamento das rochas. O conhecimento adquirido sobre as características e a distribuição da silicificação nestes depósitos carbonáticos é importante, especialmente quando se considera que a Formação La Silla, na Província de San Juan, é a formação mais minerada para a produção de calcário.